WBG Support for Tourism Clients and Destinations During the COVID-19 Crisis - World Bank Group (World Bank, Washington, DC, 2020)
WBG support for tourism clients and destinations during the COVID-19 crisis in the form of planning and communication, reducing tax burdens, contamination support, generating alternative revenues, minimizing revenue loss, redeploying assets, and other.